The Importance of Educational Service Quality for Customer Satisfaction and Organizational Reputation - Ramovš, Marjeta; Milfelner, Borut (Naše gospodarstvo/Our economy, 2023)
This paper aims to enhance the understanding of the concepts of service quality, customer satisfaction with service, and organizational reputation in the context of educational services. The conceptual framework for testing the relationship between the three constructs was developed and tested on a sample of 97 educational service users. The results showed no signifi- cant difference between perceived and expected service quality. However, a positive relationship was found between customer satisfaction and three subconstructs of perceived service quality. Also, a significant positive cor- relation between organizational reputation and three latent variables of perceived service quality and a positive relationship between satisfaction and organizational reputation.